2022
DOI: 10.1101/2022.05.18.492404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gene Novelties in Amphioxus Illuminate the Early Evolution of Deuterostomes

Abstract: Horizontal gene transfer (HGT) enables novel gene establishment but has rarely been reported in the genomes of deuterostomes. Using the genomes of four amphioxi, massive HGT events were identified that introduced novel genes in different functional groups. Innate immunity of amphioxi that have no adaptative immune system was enriched by HGT genes. Anaerobic adaptation of amphioxi may have been enabled by the HGT of genes for alcohol dehydrogenase and ferredoxin. A proximally arrayed cluster of EF-hand calcium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 135 publications
0
2
0
Order By: Relevance
“…Genome sequencing and de novo genome assembly of B. belcheri beihai has been reported [37]. In brief, the genomic DNA was sequenced by Illumina HiSeq 2000 in 500-bp and 3000-bp libraries to generate paired-end NGS short reads and PacBio RS system for third-generation long reads.…”
Section: Genome Sequencing and De Novo Genome Assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Genome sequencing and de novo genome assembly of B. belcheri beihai has been reported [37]. In brief, the genomic DNA was sequenced by Illumina HiSeq 2000 in 500-bp and 3000-bp libraries to generate paired-end NGS short reads and PacBio RS system for third-generation long reads.…”
Section: Genome Sequencing and De Novo Genome Assemblymentioning
confidence: 99%
“…In this study, the adult Beihai amphioxus was suggested as a B. belcheri subspecies and was tentatively named B. belcheri beihai. A high-quality B. belcheri beihai genome was assembled and annotated by our team [37]. A total of 347 HFs in the B. belcheri beihai genome were identified, and the genomic features of the HFs were analyzed.…”
Section: Introductionmentioning
confidence: 99%